2015
DOI: 10.1007/s11205-015-1195-z
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Self Perceived Health Among European Older Adults

Abstract: There is increasing interest among researchers in the effects of social capital on the health of older adults. One of the key policy question for an ageing population concerns how do we identify the factors that influence health. Very recently, an increasing interest on social capital as a key determinant for health has developed and, surprisingly, not much is known for the European population. This paper analyzes the association between social capital and self-perceived health among older adults in Europe usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…However, the differences among the two groups were not statistically significant. In other words, older adults that were socially isolated from their family and friends were shown to be less likely to enjoy good health, both physically and mentally, confirming the results of previous studies (Arezzo & Giudici, 2017;Auslander & Litwin, 1991;Golden et al, 2009;Kim, 2001). This may highlight a crucial role of informal social networks in maintaining good health during later life, beyond community environments.…”
Section: Discussionsupporting
confidence: 87%
“…However, the differences among the two groups were not statistically significant. In other words, older adults that were socially isolated from their family and friends were shown to be less likely to enjoy good health, both physically and mentally, confirming the results of previous studies (Arezzo & Giudici, 2017;Auslander & Litwin, 1991;Golden et al, 2009;Kim, 2001). This may highlight a crucial role of informal social networks in maintaining good health during later life, beyond community environments.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the wide use of self-rated health measurements and several studies examining associations between self-rated health and various factors, it is still unclear what the self-rated health captures [ 4 , 5 , 12 , 21 ]. Due to the central role of self-rated health in age-related challenges and risks, reported in our prior study [ 20 ] and other studies [ 10 , 12 ], we anticipate that new knowledge about factors associated with self-rated health may contribute to increase the efficiency of PHVs. This knowledge could enhance the opportunities to support necessary changes in the older person’s life and thereby improve self-rated health [ 8 ].…”
Section: Introductionmentioning
confidence: 98%
“…There are several factors associated with self-rated health, such as the demographic factors gender and education. In a European study with 40,229 individuals aged ≥60, living in 16 countries, 53% of the total sample rated their health as good; 51% of the women and 56% of the men [ 10 ]. The tendency of women rating their health poorer than men has also been shown in a longitudinal study in Norway [ 11 ] as well as in a prospective study with data from Europe and USA [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…we found significant associations with both preference for participation and degree of commitment. Perhaps the wish to use health con- Furthermore, Omariba and Ng (2011) reported that those who had higher health literacy expressed higher self-rated health, which is also associated with social capital (Arezzo & Giudici, 2017;O'Doherty, French, Steptoe, & Kee, 2017). The Japanese Ministry of Health, Labour and Welfare stated that social factors consisted of connection, reliance and social participation; higher self-rated health leads to higher social capital, and, in turn, increases preference for participation, degree of commitment and social participation.…”
Section: Discussionmentioning
confidence: 99%